Submissive to the Political Will? Civil Society and Victims Mobilization around Truth Commissions - Carles Fernandez Torne (Universidad de Los Andes, 2019)
Objective/context: The article explores truth commissions as processes that allow victims and civil society mobilization. It examines the relationship between victims and civil society with the governing regime in the lead up to the establishment of a truth commission and in the implementation of a commissions recommendations. The article frames mobilization as enabling vertical accountability relationships following the pressure that victims and civil society exert on the governing regime. To support this argument, I examine the commissions established in 1990 in Nepal and in 1994 in Sri Lanka. Methodology: The article proposes evaluative criteria showing a governing regime is rendered accountable to pressure from civil society, in the lead up to establishing a truth commission and as a result of the recommendations in the final report. It then assesses whether or not the data collected fulfills the evaluative criteria proposed. Data has been collected by carrying out a literature review, including primary and secondary sources, and through semi-structured interviews conducted in Nepal and Sri Lanka between 2013 and 2015. Conclusions: The evidence collected suggests that a close relationship between victims, civil society, and pro-democracy political parties leading to the establishment of a truth commission, limits the pressure this civil society can exert on the implementation of recommendations, once those pro-democracy political parties are in the new government. Originality: The analysis of truth commissions as processes is relevant to better understand the reasons behind a lack of implementation of their recommendations.